2023
DOI: 10.1021/acsomega.2c05513
|View full text |Cite
|
Sign up to set email alerts
|

g-C3N4 Nanosheet Supported CuO Nanocomposites for the Electrochemical Carbon Dioxide Reduction Reaction

Abstract: We have prepared CuO-derived electrocatalysts on a graphitic carbon nitride (g-C 3 N 4 ) nanosheet support for the electrochemical carbon dioxide reduction reaction (CO 2 RR). Highly monodisperse CuO nanocrystals made by a modified colloidal synthesis method serve as the precatalysts. We use a two-stage thermal treatment to address the active site blockage issues caused by the residual C18 capping agents. The results show that the thermal treatment effectively removed the capping agents and increased the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…Converting carbon dioxide (CO 2 ) into valuable chemicals and fuels has made an impact on reducing our carbon footprint. However, the high stability of CO 2 for conversion into different chemicals restricts the application. Therefore, the research community has focused on developing materials and systems for efficient CO 2 conversion by reducing the high activation energy of CO 2 . It is possible to achieve CO 2 reduction via various routes, including photocatalytic and electrochemical conversion. In this way, besides decreasing carbon emissions, value-added chemicals, such as methanol, hydrogen, formic acid, and syngas, can be produced. Among these chemicals, formic acid stands out as an alternative to fossil fuels due to its advantages, such as being an energy-intensive material, having a high volumetric hydrogen density, and having enormous potential as an effective hydrogen storage vector . Typically, the most important factor in producing different types of chemicals, from formic acid to carbon monoxide and multicarbon hydrocarbons and oxygenates, is the selectivity of the used catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Converting carbon dioxide (CO 2 ) into valuable chemicals and fuels has made an impact on reducing our carbon footprint. However, the high stability of CO 2 for conversion into different chemicals restricts the application. Therefore, the research community has focused on developing materials and systems for efficient CO 2 conversion by reducing the high activation energy of CO 2 . It is possible to achieve CO 2 reduction via various routes, including photocatalytic and electrochemical conversion. In this way, besides decreasing carbon emissions, value-added chemicals, such as methanol, hydrogen, formic acid, and syngas, can be produced. Among these chemicals, formic acid stands out as an alternative to fossil fuels due to its advantages, such as being an energy-intensive material, having a high volumetric hydrogen density, and having enormous potential as an effective hydrogen storage vector . Typically, the most important factor in producing different types of chemicals, from formic acid to carbon monoxide and multicarbon hydrocarbons and oxygenates, is the selectivity of the used catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that g-C3N4 can be combined with other semiconductors, such as Fe3O4 [23,24], CdS [25,26], ZnO [27,28], TiO2 [29], and CuO [30][31][32][33]. This coupling technique aims to enhance the separation efficiency of photogenerated electron/hole pairs, hence improving photocatalytic activity [19,21,22].…”
Section: Introductionmentioning
confidence: 99%